Progress in synthesis, modification, characterization and applications of hyperbranched polyphosphate polyesters - Dongyan Hao; Xiaoxiao Guo; Xing Zhu; Chao Wei; Lanchang Gao; Xuechuan Wang (Designed Monomers and Polymers)
Hyperbranched polyphosphate polyesters (HPPs) as a special class of hyperbranched polymers have attracted increased interest and have been intensively studied, because of peculiar structures, excellent biocompatibility, flexibility in physicochemical properties, biodegradability, water soluble, thermal stability, and mechanical properties. HPPs can be divided into phosphates as monomers and phosphates as end groups. In this article, the classification, general synthesis, modifications, and applications of HPP are reviewed. In addition, recent developments in the application of HPP are described, such as modified or functionalized by end capping and hypergrafting to improve the performances in polymer blends, coatings, flame retardant, leather. Furthermore, the modifications and application of HPPs in biomedical materials, such as drug delivery and bone regeneration were discussed. In summary, the hyperbranched polymer enlarges its application range and improves its application performance compared with conventional polymer. In the future, more new HPPs composite materials will be developed through hyperbranched technique. This review of HPPs will provide useful theoretical basis and technical support for the development of new hyperbranched polymer material.